Dexmedetomidine Protects Human Cardiomyocytes Against Ischemia-Reperfusion Injury Through α2-Adrenergic Receptor/AMPK-Dependent Autophagy - Xiao, Yingying; Li, Junpeng; Qiu, Lisheng; Jiang, Chuan; Huang, Yanhui; Liu, Jinfen; Sun, Qi; Hong, Haifa; Ye, Lincai (Frontiers in Pharmacology, 2021)
Background: Ischemia-reperfusion injury (I/R) strongly affects the prognosis of children with complicated congenital heart diseases (CHDs) who undergo long-term cardiac surgical processes. Recently, the α2-adrenergic receptor agonist Dexmedetomidine (Dex) has been reported to protect cardiomyocytes (CMs) from I/R in cellular models and adult rodent models. However, whether and how Dex may protect human CMs in young children remains largely unknown. Methods and Results: Human ventricular tissue from tetralogy of Fallot (TOF) patients and CMs derived from human-induced pluripotent stem cells (iPSC-CMs) were used to assess whether and how Dex protects human CMs from I/R. The results showed that when pretreated with Dex, the apoptosis marker-TUNEL and cleaved caspase 3 in the ventricular tissue were significantly reduced. In addition, the autophagy marker LC3II was significantly increased compared with that of the control group. When exposed to the hypoxia/reoxygenation process, iPSC-CMs pretreated with Dex also showed reduced TUNEL and cleaved caspase 3 and increased LC3II. When the autophagy inhibitor (3-methyladenine, 3-MA) was applied to the iPSC-CMs, the protective effect of Dex on the CMs was largely blocked. In addition, when the fusion of autophagosomes with lysosomes was blocked by Bafilomycin A1, the degradation of p62 induced by Dex during the autophagy process was suspended. Moreover, when pretreated with Dex, both the human ventricle and the iPSC-CMs expressed more AMP-activated protein kinase (AMPK) and phospho AMPK (pAMPK) during the I/R process. After AMPK knockout or the use of an α2-adrenergic receptor antagonist-yohimbine, the protection of Dex and its enhancement of autophagy were inhibited. Conclusion: Dex protects young human CMs from I/R injury, and α2-adrenergic receptor/AMPK-dependent autophagy plays an important role during this process. Dex may have a therapeutic effect for children with CHD who undergo long-term cardiac surgical processes.